Financial risk management based on functional data analysis. (18th August 2018) - Cai, Tianming
Abstract: Financial risk management is of great significance in modern society. The method of functional data analysis is extended to the research on financial market risk measurement, and a new research perspective and analytical tool is provided for better grasping the change law of financial market fluctuation and exploring the potential structure and dynamic changes of financial assets risk. Taking the stock market as an example, a systematic and detailed analysis of the risk measurement of China's financial market is made, and it provides a new empirical evidence to better know and understand the risk of China's financial market. The important ideas of functional data analysis, time series analysis and statistical algorithms are combined and applied it to the study of risk measurement in financial risk management. The empirical analysis shows that China's stock market not only changes the average level of risk changes, but also changes the main change factors of risk changes.